Estudio de la aplicación de las tecnologías de la información y la comunicación en la Dirección Administrativa del Gobierno Autónomo Descentralizado Municipal del Cantón Loja en el periodo 2011 – 2012 - Vicente Camizán, Leimer René (2016)
The present research work is entitled "Study of the application of information and communication technologies in the Administrative Office of the Autonomous Decentralized Government of Loja in the 2011 – 2012 academic period" The evolution of information and communications technologies have entered our daily lives, at the present this is a remarkable fact that is immediately perceived when to use them and apply them in different activities such as commercial, academic, social, cultural, sports , economic and special humanists. These have enabled most people to interact and manipulate, to form a partnership network with the ease and flexibility to communicate and inform news that are happening at local, national and different places around the world. Within the Government of Loja computer tools that are being used are the internet, intranet, quipux, government revenue system, website, email and other (program zero papers). Those tools are fully operational in each of the various directorates of the government of Loja. Have incorporated the ICT (information and communication´ technologies) within the Government of Loja, it is how great they are and their importance, which are mainly aimed at providing a better quality service, efficient and timely taxpayers, those who need to be well informed when they visit the GAD (Autonomous Decentralized Government) to complete the formalities of a more transparent and faster service. 5 This research work is carried out in order to conduct a study on the practical use of technological tools, see if ICT have created a more efficient and quality service to taxpayers, which is able to avoid and save time and space with the desire to provide economic returns for the province and country with a good management and implementation within the Administrative Office of the Autonomous Decentralized Government of Loja.